2000
DOI: 10.1088/0964-1726/9/6/322
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a MEMS-IDT gyroscope

Abstract: The design, development and performance evaluation of a novel radio frequency microelectromechanical systems (MEMS) gyroscope, based on a surface acoustic wave resonator (SAWR) and a surface acoustic wave sensor is presented in this paper. Most of the MEMS gyroscopes based on silicon vibratory structures that utilize the energy transfer between the two vibratory modes demand small fabrication tolerances to minimize signal output when there is no rotation (i.e. zero rate output). This 1 cm × 1 cm gyroscope oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…On the other hand, a SAW-based sensor has not only the superior benefits of inherent shock robustness because of employing no moving mechanical parts but also the simplicity of the fabrication process. Two types of SAWbased gyroscopes, using the standing wave and the propagating wave, have been demonstrated [3][4][5][6]. Though a device using the standing wave showed meaningful performance as a rate sensor, it still had to overcome a substantial temperature drift owing to using a strong piezoelectric coupling material.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a SAW-based sensor has not only the superior benefits of inherent shock robustness because of employing no moving mechanical parts but also the simplicity of the fabrication process. Two types of SAWbased gyroscopes, using the standing wave and the propagating wave, have been demonstrated [3][4][5][6]. Though a device using the standing wave showed meaningful performance as a rate sensor, it still had to overcome a substantial temperature drift owing to using a strong piezoelectric coupling material.…”
Section: Introductionmentioning
confidence: 99%
“…According to their functional principles, SAW gyroscopes are categorized into different types such as standing-wave-mode type gyroscopes, progressive-wave-mode type gyroscopes, and multi-axis detectable SAW gyroscopes, all of which are introduced in this article [10][11][12][13][14][15][16][17][18][19].…”
Section: Reviewmentioning
confidence: 99%
“…This type of SAW gyroscope has unique properties such as superior inherent shock and vibration robustness, easy resonance frequency matching between the drive and sense modes, low power consumption, and facile wireless circuit implementation [5][6][7][8]. To date, few research groups have reported on SAW-based gyroscopes that have different designs and structures [9][10][11][12][13][14]. Varadan et al reported a 74.2-MHz MEMS-IDT SAW gyroscope [12], and Kurosawa et al demonstrated the effect of the metal dot array design on the gyroscope's performance [13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few research groups have reported on SAW-based gyroscopes that have different designs and structures [9][10][11][12][13][14]. Varadan et al reported a 74.2-MHz MEMS-IDT SAW gyroscope [12], and Kurosawa et al demonstrated the effect of the metal dot array design on the gyroscope's performance [13]. Lee et al presented a micro rate gyroscope, based on the SAW gyroscopic effect on ST quartz that used a differential dual-delay-line oscillator configuration [14].…”
Section: Introductionmentioning
confidence: 99%